Negative pole piece, secondary battery, electric device, artificial graphite and preparation method thereof
By using specially made artificial graphite in the negative electrode sheet of the secondary battery, the gram capacity and compaction density of the negative electrode active material are improved, and the problem of insufficient energy density of the existing secondary battery is solved, thereby achieving high energy density and excellent application performance.
Patent Information
- Application Number
- CN202411214854.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-04-18
AI Technical Summary
The existing secondary batteries have shortcomings in terms of energy density and cannot meet the increasingly high application needs.
A negative electrode sheet is adopted, including a negative electrode current collector and an anode film layer. The negative electrode film layer is composed of artificial graphite. The La (110) of artificial graphite is 130nm-175nm and Lc (002) is 30nm-42nm. Through this structure, the gram capacity and compaction density of the negative electrode active material are improved, thereby increasing the energy density of the secondary battery.
The high energy density of the secondary battery is achieved, and the battery's range and application efficiency are improved.
Smart Images

Figure BDA0005022404060000191 
Figure BDA0005022404060000211 
Figure BDA0005022404060000212
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a negative electrode sheet, a secondary battery, an electrical device, artificial graphite and a preparation method thereof. Background Art
[0002] In recent years, as the application scope of secondary batteries has become more and more extensive, secondary batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, aerospace and other fields. With the rapid development of secondary batteries, people have also put forward higher requirements for their energy density. Summary of the invention
[0003] The present application is made in view of the above-mentioned problems, and its purpose is to provide a negative electrode sheet, a secondary battery, an electric device, artificial graphite and a preparation method thereof. The secondary battery of the present application has a high energy density.
[0004] In order to achieve the above-mentioned object, the present application provides a negative electrode sheet, including a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material, wherein the negative electrode active material includes artificial graphite, the La(110) of the artificial graphite is 130nm-175nm, and the Lc(002) is 30nm-42nm, La(110) represents the crystallite size along the a-axis in the (110) crystal plane of the artificial graphite, and Lc(002) can represent the crystallite size along the c-axis in the (002) crystal plane of the artificial graphite. In the present application, the graphite grains in the artificial graphite are well developed, which is conducive to the embedding of active ions, thereby being able to increase the gram capacity and compaction density of the negative electrode active material, thereby increasing the energy density of the secondary battery.
[0005] In some embodiments, the La(110) of the artificial graphite is 132nm-172nm, and the Lc(002) is 30nm-36nm. This is beneficial to improving the gram capacity and compaction density of the negative electrode active material, thereby facilitating the secondary battery to have a high energy density.
[0006] In some embodiments, La(110) / Lc(002) is 3.5-5.5, which is beneficial to increase the gram capacity of the negative electrode active material and improve the energy density of the secondary battery.
[0007] In some embodiments, La(110) / Lc(002) is 4.5-5.5.
[0008] In some embodiments, a charge and discharge test is performed on a button cell prepared from the artificial graphite at a lithium removal rate of 0.1C and a lithium insertion rate of 0.05C, respectively, to obtain a charge and discharge curve in the range of 0.005V-2.0V. In the discharge curve, there is a lithium insertion platform in the voltage range of 0.005V to 0.070V, and the discharge capacity corresponding to the lithium insertion platform accounts for more than 43% of the total discharge capacity of the button cell. As a result, the artificial graphite has a high gram capacity, which is beneficial to improving the energy density of the secondary battery.
[0009] In some embodiments, the ratio X of the discharge capacity corresponding to the lithium embedded platform to the total discharge capacity of the button cell is 43%-47%.
[0010] In some embodiments, the gram capacity of the artificial graphite is 359 mAh / g or more, which is beneficial to improve the energy density of the secondary battery. In some embodiments, the gram capacity of the artificial graphite is 359 mAh / g-366 mAh / g.
[0011] In some embodiments, the degree of graphitization of the artificial graphite is 94.0%-96.0%. This is beneficial for the artificial graphite to have a high compaction density and gram capacity, thereby improving the energy density of the secondary battery. In some embodiments, the degree of graphitization of the artificial graphite is 94.2%-95.8%.
[0012] In some embodiments, the artificial graphite has a powder compaction density of 1.95-2.04 g / cc under a pressure of 50000 N. This is beneficial for improving the energy density of the secondary battery.
[0013] In some embodiments, the artificial graphite includes secondary particles.
[0014] In some embodiments, the volume distribution particle size Dv50 of the artificial graphite is 14.5 μm-18.0 μm, which is beneficial to improve the energy density of the secondary battery.
[0015] In some embodiments, the particle size distribution of the artificial graphite is (Dv90-Dv10) / Dv50 of 0.9-1.25.
[0016] In some embodiments, the specific surface area of the artificial graphite is 0.8 m 2 / g-2.1m 2 / g. On the one hand, it is beneficial to reduce the activity of surface side reactions and improve the initial coulombic efficiency of secondary batteries. On the other hand, it is beneficial to improve the transport performance of active ions and improve the kinetic performance of secondary batteries.
[0017] The second aspect of the present application also provides a secondary battery, comprising the negative electrode plate of the first aspect. Therefore, the secondary battery of the present application has a high energy density.
[0018] The third aspect of the present application also provides an electric device, comprising the secondary battery of the second aspect. Since the electric device of the present application comprises the secondary battery provided by the present application, it has at least the same advantages as the secondary battery.
[0019] The fourth aspect of the present application also provides an artificial graphite, wherein the La(110) of the artificial graphite is 130nm-175nm, and the Lc(002) is 30nm-42nm, La(110) represents the crystallite size along the a-axis in the (110) crystal plane of the artificial graphite, and Lc(002) may represent the crystallite size along the c-axis in the (002) crystal plane of the artificial graphite. The artificial graphite is conducive to the embedding of active ions, and can improve the gram capacity and compaction density of the negative electrode active material.
[0020] In some embodiments, La(110) / Lc(002) is 4.5-5.5.
[0021] In some embodiments, a button cell prepared from the artificial graphite is subjected to charge and discharge tests at a lithium desorption rate of 0.1C and a lithium insertion rate of 0.05C, respectively, to obtain a charge and discharge curve in the range of 0.005V-2.0V. In the discharge curve, there is a lithium insertion platform in the voltage range of 0.005V to 0.070V, and the discharge capacity corresponding to the lithium insertion platform accounts for a proportion X of more than 43% of the total discharge capacity of the button cell.
[0022] In some embodiments, the gram capacity of the artificial graphite is greater than 359 mAh / g.
[0023] In some embodiments, the artificial graphite has a graphitization degree of 94.0%-96.0%.
[0024] In some embodiments, the artificial graphite has a powder compaction density of 1.95 g / cc-2.04 g / cc under a pressure of 50,000 N.
[0025] In some embodiments, the artificial graphite includes artificial graphite secondary particles.
[0026] The fifth aspect of the present application also provides a method for preparing artificial graphite, which comprises the following steps:
[0027] Pretreatment step: crushing and shaping the calcined needle coke to obtain a shaped material, wherein the calcined needle coke has a carbon content of more than 97%, a volatile component content of less than 2%, and a sulfur content of less than 0.5%;
[0028] Granulation step: mixing the shaping material with a granulating agent to obtain a granulated material;
[0029] Graphitization step: graphitizing the granulated material at 3000° C.-3200° C. to obtain the artificial graphite with La(110) of 130nm-175nm and Lc(002) of 30nm-42nm.
[0030] By adopting the above method and using raw materials with higher purity to prepare artificial graphite, it is beneficial to reduce the number of impurities and defects in the artificial graphite, improve the graphitization degree and La (110) value of the artificial graphite, and then increase the gram capacity and compaction density of the negative electrode film layer, and improve the energy density of the secondary battery.
[0031] In some embodiments, the softening point of the granulating agent is 180° C.-270° C. The granulating agent has strong adhesiveness, which is beneficial to reducing the amount of the granulating agent and improving the gram capacity and compaction density of the artificial graphite.
[0032] In some embodiments, the coking value of the granulating agent is 50-70%, which is beneficial to increase the gram capacity and compaction density of artificial graphite and improve the energy density of secondary batteries.
[0033] In some embodiments, the mass ratio of the shaping material to the granulating agent is 100:(6-12). This is beneficial to improving the energy density of the secondary battery.
[0034] In some embodiments, the preparation method further comprises: before the graphitization step, pre-carbonizing the granulated material to obtain an intermediate. The pre-carbonization step is beneficial to reducing the number of impurities and defects in the artificial graphite, thereby increasing the gram capacity and compaction density of the artificial graphite and increasing the energy density of the secondary battery.
[0035] In some embodiments, the pre-carbonization treatment is performed at a temperature of 1000-1500° C. for a time of 1-4 hours.
[0036] In some embodiments, the preparation method further comprises: after the graphitization step, subjecting the artificial graphite to a surface micro-oxidation treatment, thereby facilitating the improvement of the compaction density of the artificial graphite powder and thus improving the energy density of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is a schematic diagram of a battery cell according to an embodiment of the present application.
[0038] Figure 2 yes Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown.
[0039] Figure 3is a schematic diagram of a battery module according to an embodiment of the present application.
[0040] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0041] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0042] Figure 6 Schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.
[0043] Figure 7 It is a charge and discharge curve diagram of the negative electrode sheet according to one embodiment of the present application.
[0044] Figure 8 yes Figure 7 An enlarged view of the charge and discharge curve in the voltage range of 0.005V-0.5V.
[0045] Description of reference numerals:
[0046] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION
[0047] Below, the embodiments of the negative electrode plate, secondary battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0048] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0049] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0050] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0051] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0052] If not specifically stated, the terms used in this application have the commonly known meanings generally understood by those skilled in the art.
[0053] If not otherwise specified, the values of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.
[0054] If not otherwise specified, in the present application, the term "active ions" refers to ions that can be intercalated and extracted back and forth between the positive electrode and the negative electrode of a secondary battery, including but not limited to lithium ions.
[0055] At present, the development of electric vehicles has put forward higher requirements for battery life, so the demand for battery energy density is constantly increasing. In order to obtain secondary batteries with high energy density, it has been reported that graphite materials are obtained by mixing artificial graphite raw materials with flake graphite and then graphitizing them. However, the high degree of graphitization of flake graphite makes it easy for graphite sheets to peel off during the cycle, and flake graphite will have a large volume expansion, which not only deteriorates the cycle performance, but also is not conducive to the energy density of secondary batteries.
[0056] Based on this, the present application proposes a negative electrode plate, a secondary battery, an electrical device, an artificial graphite and a preparation method thereof, thereby enabling the secondary battery to have a high energy density.
[0057] Negative electrode
[0058] The present application proposes a negative electrode plate, comprising a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, wherein the negative electrode film layer comprises a negative electrode active material, wherein the negative electrode active material comprises artificial graphite, wherein La(110) of the artificial graphite is 130nm-175nm, and Lc(002) is 30nm-42nm, wherein La(110) represents the crystallite size along the a-axis in the (110) crystal plane of the artificial graphite, and Lc(002) represents the crystallite size along the c-axis in the (002) crystal plane of the artificial graphite.
[0059] In the present application, the increase in La of artificial graphite indicates that the size of artificial graphite crystallites increases, and the number of sites that can be embedded with lithium on the surface of artificial graphite increases, so that the gram capacity increases. In addition, the increase in crystallite size can also reduce the number of grain boundaries of artificial graphite crystallites, so that the number of sites that can be embedded with lithium increases, thereby reducing the adverse effects of gram capacity and powder compaction density, thereby improving the gram capacity and powder compaction density of artificial graphite. The Lc of artificial graphite is within the above range, which is conducive to reducing the stacking of graphite crystallites, thereby reducing the number of grain boundaries between crystallites, and is conducive to increasing the number of lithium embedded sites on the surface of artificial graphite, thereby improving the gram capacity of artificial graphite. By making the La (110) of artificial graphite 130nm-175nm, and Lc (002) 30nm-42nm, the development of graphite grains in the material is better, which is conducive to the embedding of active ions, thereby improving the gram capacity and compaction density of negative electrode active materials, thereby improving the energy density of the battery.
[0060] The La(110) of the artificial graphite is 130nm-175nm, and Lc(002) is 30nm-42nm. Exemplarily, La(110) is 130nm, 135nm, 140nm, 145nm, 150nm, 155nm, 160nm, 165nm, 170nm, 172nm, 173nm, 175nm or a value between the ranges formed by any two of them, and Lc(002) is 30nm, 31nm, 32nm, 33nm, 34nm, 35nm, 36nm, 37nm, 38nm, 39nm, 40nm, 41nm, 42nm or a value between the ranges formed by any two of them. Optionally, the La(110) of the artificial graphite is 132nm-172nm, and Lc(002) is 30nm-36nm. By making the La(110) and Lc(002) of the artificial graphite within the above range, it is more conducive to improving the gram capacity and compaction density of the negative electrode active material, thereby facilitating the secondary battery to have a high energy density.
[0061] In the present application, in the X-ray diffraction spectrum of the artificial graphite, there is no obvious characteristic peak corresponding to the (101) crystal plane of the 3R phase in the range of 2θ of 43-44°, and the particle structure of the artificial graphite is a dense block structure.
[0062] In some embodiments, the La(110) / Lc(002) of the artificial graphite is 3.5-5.5. In the present application, by making the La(110) / Lc(002) of the artificial graphite within the above range, the number of crystallites in the graphite material is small, so the number of grain boundaries between the grains is small, which is beneficial to increase the lithium embedding sites on the surface of the artificial graphite, thereby facilitating the increase of the gram capacity of the negative electrode active material, thereby improving the energy density of the secondary battery. Exemplarily, La(110) / Lc(002) can be 3.5, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8, 5.0, 5.2, 5.5 or a value between the ranges consisting of any two of them. In some optional embodiments, in the artificial graphite, La(110) / Lc(002) is 4.5-5.5.
[0063] In some embodiments, a button cell prepared from the artificial graphite is subjected to charge and discharge tests at a delithiation rate of 0.1C and a lithium insertion rate of 0.05C, respectively, to obtain a charge and discharge curve in the range of 0.005V-2.0V. In the discharge curve, there is a lithium insertion platform in the voltage range of 0.005V-0.07V, and the proportion X of the discharge capacity corresponding to the lithium insertion platform to the total discharge capacity of the button cell is greater than 43%.
[0064] In the present application, the charge and discharge test is carried out by the following method: the sample powder is mixed evenly with the conductive agent carbon black (SuperP), the binder polyvinylidene fluoride (PVDF) and the solvent N-methylpyrrolidone (NMP) in a mass ratio of 91.6:1.8:6.6 to prepare a slurry; the prepared slurry is coated on the surface of the negative electrode current collector copper foil, and dried in an oven for use; ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare a concentration of 1 mol / L electrolyte; then, a metal lithium sheet is used as a counter electrode, a polyethylene (PE) film is used as an isolation membrane, and the above-mentioned electrolyte is assembled into a CR2430 button cell in an argon-protected glove box; after the obtained button cell is allowed to stand for 12 hours, it is discharged at a constant current rate of 0.05C at 25°C to 0.005V, allowed to stand for 10 minutes, and then discharged at a constant current of 50μA again to 0.005V, allowed to stand for 10 minutes, and finally discharged at a current of 10μA to 0.005V, and the charging process is charged to 2.0V at a rate of 0.1C to obtain the relationship between the charge and discharge capacity and voltage of the artificial graphite, that is, the charge and discharge curve.
[0065] In the present application, button cells made of artificial graphite are subjected to the above-mentioned charge and discharge test to obtain a charge and discharge curve. In the discharge curve, the discharge capacity corresponding to the lithium insertion platform in the voltage range of 0.005V-0.07V accounts for more than 43% of the total discharge capacity of the button cell. The artificial graphite has a high gram capacity, which is beneficial to improve the energy density of the secondary battery. Although the mechanism is not clear, the inventors believe that during the lithium insertion process of the graphite material, as the amount of lithium ion insertion increases, graphite intercalation compounds of different orders, such as LiC24, LiC12, LiC6, etc., will gradually form. The formation of graphite intercalation compounds of different orders corresponds to lithium insertion platforms in different voltage ranges in the charge and discharge curve of the graphite material. Since the theoretical capacity of graphite intercalation compounds of different orders is different, for example, the theoretical capacity of LiC6 is 372mAh / g, while the theoretical specific capacity of LiC12 is 186mAh / g. Therefore, in the lithium insertion process, the more LiC6 (i.e., the lithium insertion platform corresponding to the voltage range of 0.005-0.07V) is formed, the more the corresponding capacity contribution is, and the higher the gram capacity of the graphite material is. Exemplarily, the ratio X can be 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50% or a value between the ranges consisting of any two of them. In some embodiments, the proportion X of the discharge capacity corresponding to the lithium insertion platform to the total discharge capacity of the button battery is 43%-50%, optionally 43%-47%.
[0066] In some embodiments, the gram capacity of the artificial graphite is 359mAh / g or more. By making the gram capacity of the artificial graphite within the above range, it is beneficial to increase the gram capacity of the negative electrode film layer, thereby increasing the energy density of the secondary battery. Exemplarily, the gram capacity of the artificial graphite can be 359mAh / g, 360mAh / g, 361mAh / g, 362mAh / g, 363mAh / g, 364mAh / g, 365mAh / g, 366mAh / g, 367mAh / g, 368mAh / g, 369mAh / g, 370mAh / g or a value between the ranges consisting of any two of them. Optionally, the gram capacity of the artificial graphite is 360mAh / g to 366mAh / g.
[0067] In some embodiments, the degree of graphitization of the artificial graphite is 94.0%-96.0%. By making the degree of graphitization of the artificial graphite within the above range, it is beneficial for the artificial graphite to have a high compaction density and gram capacity, thereby improving the energy density of the secondary battery. Exemplarily, the degree of graphitization of the artificial graphite can be 94.0%, 94.5%, 95.0%, 95.5%, 96.0% or a value between the ranges consisting of any two of them. In some optional embodiments, the degree of graphitization of the artificial graphite is 94.2%-95.8%.
[0068] In some embodiments, the powder compaction density of the artificial graphite under a pressure of 50000N is 1.95-2.04g / cc. By making the powder compaction density of the artificial graphite within the above range, it is beneficial to increase the compaction density of the negative electrode film layer, thereby increasing the energy density of the secondary battery. Exemplarily, the powder compaction density of the artificial graphite under a pressure of 50000N can be 1.95g / cc, 1.96g / cc, 1.97g / cc, 1.98g / cc, 1.99g / cc, 2.00g / cc, 2.01g / cc, 2.02g / cc, 2.03g / cc, 2.04g / cc or a value between any two of them.
[0069] In some embodiments, the artificial graphite includes secondary particles, which is beneficial to reducing the orientation of the structure, buffering the volume change during the cycle, and facilitating structural stability, thereby improving life performance.
[0070] In some embodiments, the volume distribution particle size Dv50 of the artificial graphite is 14.5μm-18.0μm. By making the volume distribution particle size Dv50 of the artificial graphite in the above range, it is beneficial for the artificial graphite to have a high gram capacity and a high powder compaction density, which is beneficial to improve the energy density of the secondary battery. Exemplarily, the volume distribution particle size Dv50 of the artificial graphite can be 14.5μm, 15.0μm, 15.5μm, 16.0μm, 16.5μm, 17.0μm, 17.5μm, 18.0μm or a value between the ranges consisting of any two of them. In some optional embodiments, the volume distribution particle size Dv50 of the artificial graphite is 15.0μm-17.5μm.
[0071] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the artificial graphite is 0.90-1.25. As a result, it is beneficial to improve the compaction density of the negative electrode film layer and the energy density of the secondary battery; in addition, it is also beneficial to form a reasonable pore structure between the particles of the negative electrode film layer, improve the active ion and electron transport performance in the negative electrode film layer, and thus improve the kinetic performance of the secondary battery. Exemplarily, the particle size distribution (Dv90-Dv10) / Dv50 of the artificial graphite is 0.90, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25 or a value between the ranges consisting of any two of them. In some optional embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the artificial graphite is 0.90-1.20.
[0072] In some embodiments, the specific surface area of the artificial graphite is 0.8 m 2 / g-2.1m 2 / g. By making the specific surface area of artificial graphite within the above range, on the one hand, artificial graphite can have lower surface side reaction activity, thereby reducing the consumption of active ions in SEI film formation and improving the initial coulombic efficiency of the secondary battery; on the other hand, it can also have higher active ion transport performance and improve the kinetic performance of the secondary battery. For example, the specific surface area of the artificial graphite can be 0.8m 2 / g, 1.0m 2 / g, 1.2m 2 / g, 1.4m 2 / g, 1.6m 2 / g, 1.8m 2 / g, 2.0m 2 / g, 2.1m 2 / g or a value between the ranges consisting of any two of them.
[0073] In the present application, La (110) and Lc (002) of artificial graphite can be measured using instruments and methods known in the art. For example, the negative electrode plate removed from the secondary battery can be cleaned with an organic solvent such as DMC and then dried. The cleaned negative electrode plate is then immersed in NMP for ultrasonic treatment to separate the copper foil to obtain the negative electrode material. After the negative electrode material is dried, it is calcined at 350°C-500°C, then washed with water for multiple times, and dried at 80°C to obtain the negative electrode active material. An X-ray diffractometer (such as Bruker D8 Discover) is used for testing. The test can refer to JIS K 0131-1996 and JB / T4220-2011 to obtain the peak intensity and half-maximum full width (FWHM) of the diffraction peak corresponding to the (110) crystal plane of artificial graphite, and the peak intensity and half-maximum full width (FWHM) of the diffraction peak corresponding to the (002) crystal plane, and then calculated according to the Scherrer formula.
[0074] In this application, the powder compaction density of a material (negative electrode active material, artificial graphite, etc.) is the mass of the powder per unit volume under specified conditions. It can be measured using instruments and methods known in the art. For example, it can be measured with an electronic pressure tester (for example, a UTM7305 electronic pressure tester) with reference to GB / T24533-2009. An exemplary test method is as follows: weigh 1 g of sample powder and add a bottom area of 1.327 cm 2 In the mold, the pressure is increased to 50000N, the pressure is maintained for 30s, and then the pressure is released and maintained for 10s. Then the powder compaction density of the material under the pressure of 50000N is recorded and calculated.
[0075] In this application, the volume distribution particle size Dv10, Dv50, and Dv90 of the material (such as negative electrode active material, artificial graphite, etc.) respectively represent the particle size corresponding to the cumulative volume distribution percentage of the material reaching 10%, 50%, and 90%, which can be measured using instruments and methods known in the art. For example, it can be measured with a laser particle size analyzer with reference to GB / T19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0076] In this application, the gram capacity of a material (negative electrode active material, artificial graphite, etc.) is the ratio of the capacitance that can be released by the active material to the mass of the active material, and can be tested by methods known in the art. An exemplary test method is as follows: the sample powder is mixed with a conductive agent, a binder and other optional additives in a certain mass ratio with a solvent to form a slurry; the prepared slurry is applied on the surface of the negative electrode current collector copper foil, and dried in an oven for use; the electrolytic salt is dissolved in an organic solvent to prepare an electrolyte of a certain concentration; then a metal lithium sheet is used as a counter electrode, a polyethylene (PE) film is used as a separator, and the electrolyte is assembled into a CR2430 button cell in an argon-protected glove box. After the button cell was left to stand for 12 hours, it was discharged at 0.15 mA constant current to 0.005 V at 25 ° C, left to stand for 10 minutes, and then discharged at 50 μA constant current to 0.005 V, left to stand for 10 minutes, and then discharged at 10 μA constant current to 0.005 V; then it was charged at 0.3 mA constant current to 2.0 V, and the charge capacity was recorded. The ratio of the charge capacity to the sample mass is the gram capacity of the corresponding material (negative active material, artificial graphite, etc.).
[0077] In the present application, the graphitization degree of a material (negative electrode active material, artificial graphite, etc.) is the proportion of carbon in the material in the form of a graphite structure, which can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (such as Bruker D8 Discover) can be used for testing. The test can refer to JIS K 0131-1996 and JB / T 4220-2011 to obtain the average interlayer spacing d of the C(002) crystal plane in the material crystal structure. 002 Then according to the formula g = (0.344-d 002 ) / (0.344-0.3354)×100% to calculate the graphitization degree. In the above formula, d 002 It is the average interlayer spacing of the C(002) crystal plane in the material's crystal structure expressed in nanometers (nm).
[0078] In the present application, secondary particles have the meanings known in the art. Secondary particles refer to particles in a state of aggregation formed by two or more primary particles. Among them, primary particles refer to particles in a non-agglomerated state. Primary particles and secondary particles can be distinguished by using a scanning electron microscope (SEM) image.
[0079] Preparation method of artificial graphite
[0080] The preparation method of artificial graphite in the present application comprises the following steps:
[0081] Pretreatment step: crushing and shaping the calcined needle coke to obtain a shaped material, wherein the calcined needle coke has a carbon content of more than 97%, a volatile component content of less than 2%, and a sulfur content of less than 0.5%;
[0082] Granulation step: mixing the shaping material with a granulating agent to obtain a granulated material;
[0083] Graphitization step: graphitizing the granulated material at 3000° C.-3200° C. to obtain the artificial graphite with La(110) of 130nm-175nm and Lc(002) of 30nm-42nm.
[0084] In the present application, calcined needle coke is used as raw material. The needle structure of calcined needle coke is stronger and the mosaic structure is less. Using calcined needle coke as raw material is beneficial to reduce the content of impurities in artificial graphite, thereby improving the graphitization degree of artificial graphite.
[0085] In the present application, the carbon content of the calcined needle coke is more than 97%, the volatile component content is less than 2%, and the sulfur content is less than 0.5%. Here, the so-called volatile component refers to hydrocarbons with lower molecular weight, such as light alkanes. The sulfur content and volatile components of the calcined needle coke are within the above range, the purity of the raw material is good, which is conducive to the development of grains during graphitization, reduces the number of defects in the graphitization process, and improves the graphitization degree of artificial graphite and the La (110) value of artificial graphite. By making the La (110) of artificial graphite 130nm-175nm, and Lc (002) 30nm-42nm, the development of graphite grains in the material is better, which is conducive to the embedding of active ions, thereby increasing the gram capacity and compaction density of the negative electrode film layer, and improving the energy density of the secondary battery.
[0086] In the present application, the temperature of the graphitization treatment is 3000°C-3200°C. The graphitization temperature within the above range is conducive to the growth and development of graphite grains, thereby helping to increase the La(110) value of the graphite material. In addition, it is also conducive to improving the graphitization degree of artificial graphite, thereby increasing the gram capacity of artificial graphite and the energy density of secondary batteries. Exemplarily, the graphitization temperature can be 3000°C, 3050°C, 3100°C, 3150°C, 3200°C or a value between the ranges consisting of any two of them.
[0087] In the present application, high-purity raw materials are used and the graphitization temperature is controlled at 3000°C-3200°C, which is beneficial to the development of the 110 crystal planes of the graphite grains along the a-axis during the graphitization process, thereby increasing the La (110) value of the artificial graphite. In addition, it is also beneficial to reduce the number of defects in the graphitization process, thereby facilitating the improvement of the energy density of the secondary battery.
[0088] Those skilled in the art can adjust the graphitization time as needed. For example, an Acheson graphitization furnace can be used for graphitization treatment, and when the temperature is above 2800° C., the graphitization time can be 2-8 days.
[0089] In some embodiments, the volume distribution particle size Dv50 of the shaping material is 9 μm-13 μm. Controlling the volume distribution particle size Dv50 of the shaping material within the range of 9 μm-13 μm is beneficial to reducing the number of grain boundaries between crystals in the artificial graphite, thereby increasing the gram capacity and powder compaction density of the artificial graphite.
[0090] In some embodiments, the softening point of the granulating agent is 180°C-270°C. The softening point of the granulating agent refers to the temperature at which the granulating agent is transformed from a solid state to a softened state with a certain fluidity. In the present application, the softening point can be tested using instruments and methods known in the art, for example, it can be measured with reference to GB / T4507-2014. When the softening point of the granulating agent is within the above range, the molecular weight of the polycyclic aromatic hydrocarbons in the granulating agent is large and the content is high, which is conducive to improving the cohesiveness of the granulating agent, reducing the amount of the granulating agent in the granulation step, and reducing the residual carbon content of the granulating agent, thereby increasing the gram capacity and compacted density of the artificial graphite. Exemplarily, the softening point of the above-mentioned granulating agent can be 180°C, 200°C, 220°C, 240°C, 260°C, 270°C or a value between the ranges consisting of any two of them.
[0091] In some embodiments, the coking value of the granulating agent is 50%-70%. The coking value of the granulating agent refers to the percentage of the mass of the coke residue formed after the granulating agent is heated, burned or otherwise treated under specific experimental conditions to the mass of the original sample; in the present application, the coking value can be tested by methods known in the art. Exemplarily, it can be determined with reference to GB / T 8727-2008. The coking value of the granulating agent within the above range is conducive to improving the gram capacity and compaction density of the artificial graphite, thereby improving the energy density of the secondary battery.
[0092] In some embodiments, the mass ratio of the shaping material to the granulating agent is 100:(6-12). The ratio of the shaping material to the granulating agent within the above range is conducive to reducing the residual carbon amount brought by the granulating agent, increasing the gram capacity and compaction density of the artificial graphite, and thus improving the energy density of the secondary battery.
[0093] In some embodiments, the preparation method further comprises, before the graphitization step, pre-carbonizing the granulated material to obtain an intermediate. Pre-carbonizing the granulated material is beneficial to removing volatile components in the raw material and facilitating the growth of grains in the subsequent graphitization process, thereby increasing the gram capacity and compaction density of the artificial graphite and increasing the energy density of the secondary battery.
[0094] In some embodiments, the pre-carbonization temperature is 1000-1500°C. Exemplarily, the pre-carbonization temperature can be 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, or a value between the ranges consisting of any two of them. By making the pre-carbonization temperature within the above range, the volatile components contained in the raw materials can be fully removed, which is beneficial to reduce the number of impurities and defects in the artificial graphite, thereby increasing the gram capacity of the artificial graphite. In addition, the pre-carbonization treatment can increase the density of the raw materials and increase the amount of raw materials loaded in the furnace during the graphitization process. In an optional embodiment, the pre-carbonization temperature is 1000°C-1100°C.
[0095] In some embodiments, the pre-carbonization time is 1-4 hours. Exemplary pre-carbonization time may be 1 hour, 2 hours, 3 hours, 4 hours, or a range consisting of any two of these values.
[0096] In some embodiments, the pre-carbonization is performed under a protective atmosphere. For example, the protective atmosphere may be nitrogen or argon. In an optional embodiment, the pre-carbonization is performed under a nitrogen atmosphere.
[0097] In some embodiments, the volume distribution particle size Dv50 of the intermediate is 15 μm-18 μm. The particle size of the intermediate within the above range is conducive to increasing the particle size of the artificial graphite, thereby increasing the gram capacity of the artificial graphite and the energy density of the secondary battery. Exemplarily, the volume distribution particle size Dv50 of the intermediate can be 15 μm, 16 μm, 17 μm, 18 μm or a value between the ranges consisting of any two of them.
[0098] In some embodiments, the preparation method further comprises, after the graphitization step, subjecting the artificial graphite to surface micro-oxidation treatment. In the present application, the surface micro-oxidation treatment can be carried out by methods known in the art. Exemplarily, the surface micro-oxidation treatment can be carried out by subjecting the artificial graphite to 700°C in an air atmosphere. The surface micro-oxidation treatment of artificial graphite increases the oxidized functional groups on the surface of the artificial graphite, enhances the bonding force between the particles of the artificial graphite and between the artificial graphite and the binder, reduces the rebound effect, and is beneficial to increase the powder compaction density of the artificial graphite, thereby increasing the energy density of the secondary battery.
[0099] Secondary battery
[0100] The present application also provides a secondary battery. The term "secondary battery" mentioned herein refers to a battery cell, a battery module or a battery pack. Each of these is described below.
[0101] The secondary battery cell includes a positive electrode sheet, a negative electrode sheet of the present application as described above, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0102] In addition, the secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.
[0103] Negative electrode
[0104] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0105] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0106] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0107] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0108] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0109] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0110] Positive electrode
[0111] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.
[0112] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0113] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0114] In some embodiments, when the battery cell is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.1 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0115] It should be noted that in the embodiments of the present application, the above chemical formula is the chemical formula of the material used in the secondary battery preparation process. In the positive electrode sheet, battery cell, and electrical equipment, due to the formation and circulation processes, those skilled in the art can understand that the elements in the above chemical formula may be lost. For example, in the positive electrode sheet, battery cell, and electrical equipment, due to the circulation process, the oxygen element in the positive electrode active material is lost, so the measured oxygen content in the positive electrode active material will be reduced.
[0116] It should be noted that in the positive electrode sheets, battery cells, and electrical equipment, lithium ions will be consumed during the formation and circulation processes, so the measured lithium content in the positive electrode active material will decrease. At the same time, if the positive and negative electrode sheets are supplemented with lithium, after the formation and circulation processes, the measured lithium content in the positive electrode active material will increase.
[0117] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode active materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.
[0118] In the list of positive electrode active materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.
[0119] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0120] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0121] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0122] Electrolytes
[0123] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0124] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0125] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0126] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0127] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0128] Isolation film
[0129] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0130] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0131] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0132] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0133] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0134] The present application has no particular restrictions on the shape of the battery cell, which can be cylindrical, square or any other shape. For example, Figure 1 The battery cell 5 is a square structure as an example.
[0135] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a top cover assembly 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the top cover assembly 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0136] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0137] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0138] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0139] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0140] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0141] In addition, the present application also provides an electric device, which includes a secondary battery provided in the present application. The secondary battery can be used as a power source for the electric device, or as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0142] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.
[0143] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0144] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0145] Example
[0146] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0147] Example 1
[0148] (1) Preparation of artificial graphite
[0149] Step 1: crushing and shaping the oil-based calcined needle coke raw material (carbon content of 98.5%, volatile content of 1.0%, sulfur content of 0.5%) by jet mill to obtain a shaped material with a Dv50 of 11 μm;
[0150] Step 2: Use granulating asphalt (softening point of 200°C; coking value of 60%) as a granulating agent to granulate the above-mentioned shaping material together through a granulating kettle to obtain a granulated material, wherein the mass ratio of the shaping material to the granulating agent is 100:8.
[0151] Step 3: The above-mentioned granulated material is pre-carbonized at 1150° C. for 2 hours under a nitrogen atmosphere to obtain an intermediate (the volume distribution particle size Dv50 is 16.5 μm).
[0152] Step 4: The above intermediate is graphitized at a high temperature of 3020°C, and the graphitized particles are sieved and demagnetized to obtain artificial graphite. The La(110) and Lc(002) of the material are measured based on the following measurement method, and the results are: La(110) is 131.7nm, and Lc(002) is 32.5nm.
[0153] (2) Preparation of negative electrode sheet
[0154] The artificial graphite, conductive agent Super P, thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber are fully stirred and mixed in a proper amount of solvent deionized water at a weight ratio of 96.6:0.80:1.0:1.6 to form a negative electrode slurry. The negative electrode slurry is applied on the negative electrode current collector copper foil by extrusion coating, and after drying and cold pressing, a negative electrode sheet is obtained.
[0155] (3) Preparation of positive electrode sheet
[0156] Lithium iron phosphate: conductive carbon black: PVDF = 96.2:2:1.8 was mixed in a mass ratio, and then solvent N-methylpyrrolidone was added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on both surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet was obtained.
[0157] (4) Preparation of lithium-ion batteries
[0158] A 12 μm polyethylene film was used as the separator.
[0159] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0160] The positive electrode sheet and negative electrode sheet prepared above are placed in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then the electrode assembly is obtained by winding; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and a secondary battery is obtained after vacuum packaging, standing, forming, shaping and other processes.
[0161] Embodiment 2-6
[0162] The preparation methods of Examples 2-6 are similar to those of Example 1, except that the raw materials and graphitization temperature used in the preparation steps of artificial graphite are adjusted according to the values in Table 1 below.
[0163] Comparative Examples 1-3
[0164] The preparation methods of Comparative Examples 1-3 are similar to those of Example 1, except that the raw materials and graphitization temperature used in the preparation steps of artificial graphite are adjusted according to the values in Table 1 below.
[0165] Performance Testing
[0166] The artificial graphite prepared in step (1) of the above Examples 1-6 and Comparative Examples 1-3 was tested according to the following method. The results are shown in Table 2.
[0167] Tests of La(110), Lc(002), and La / Lc of materials:
[0168] Referring to the test method of JIS K 0131-1996, the test was carried out using a Bruker D8 Discover X-ray diffractometer, in which a copper target was used as the anode target, CuKα rays were used as the radiation source, and the ray wavelength was The scanning 2θ angle range is 20°-80°, and the scanning rate is 4° / min to obtain the X-ray diffraction pattern of the powder sample. La(110) calculation formula:
[0169] Wherein: K is the shape factor, which is 1.84; λ is the wavelength (nm); β110 is the half-peak width of the 110 crystal plane corresponding to ~43° in the X-ray diffraction pattern; θ110 is the diffraction angle corresponding to the 110 crystal plane in the X-ray diffraction pattern.
[0170] Lc(002) calculation formula:
[0171] Wherein: K is the shape factor, which is 0.89; λ is the wavelength (nm); β002 is the half-peak width of the 002 crystal plane corresponding to ~26° in the X-ray diffraction spectrum; θ002 is the diffraction angle corresponding to the 002 crystal plane in the X-ray diffraction spectrum.
[0172] Test of Gram Capacity of Materials :
[0173] The prepared materials, conductive agent carbon black (Super P), binder polyvinylidene fluoride (PVDF) and solvent N-methylpyrrolidone (NMP) are mixed uniformly in a mass ratio of 91.6:1.8:6.6 to prepare a slurry; the prepared slurry is coated on the surface of the negative electrode current collector copper foil, dried in an oven and set aside; ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L; then a metal lithium sheet is used as a counter electrode and a polyethylene (PE) film is used as an isolation membrane, and the above electrolyte is assembled into a CR2430 button battery in an argon-protected glove box; the obtained button battery is left to stand for 12 hours.
[0174] At 25°C, the button cell prepared above was first discharged at a constant current of 0.15 mA to 0.005 V, allowed to stand for 5 minutes, then discharged at a constant current of 50 μA to 0.005 V, allowed to stand for 5 minutes, and then discharged at a constant current of 10 μA to 0.005 V, and the first-cycle discharge capacity of the button cell was recorded; thereafter, the button cell was charged at a constant current of 0.3 mA to 2.0 V, and the first-cycle charging capacity of the button cell was recorded. The ratio of the first-cycle charging capacity to the mass of the material is the gram capacity of the material.
[0175] The proportion of the platform's lithium-ion capacity to the total capacity is X
[0176] The CR2430 button cell was prepared by the same method as in the above-mentioned gram capacity test method. After the above-mentioned CR2430 button cell was allowed to stand for 12 hours, it was first discharged at a constant current of 0.15 mA to 0.005 V at 25°C, allowed to stand for 5 minutes, and then discharged at a constant current of 50 μA to 0.005 V again, allowed to stand for 5 minutes, and then discharged at a constant current of 10 μA to 0.005 V again; then it was charged at a constant current of 0.3 mA to 2.0 V, and the relationship between the charge and discharge capacity and voltage of the material was obtained, that is, the charge and discharge curve. The lithium insertion capacity of the lithium insertion platform that appears within 0.005V-0.070V in the discharge curve is recorded as C1, and the total lithium insertion capacity within the range of 0.005V-2.0V is recorded as C2, then the lithium insertion capacity of the platform accounts for X=C1 / C2*100%.
[0177] The charge-discharge curve of the artificial graphite material prepared in Example 1 measured by the above method is as follows: Figure 7 and Figure 8 As shown. Figure 7 and Figure 8 The lithium insertion capacity of the lithium insertion platform appearing in the range of 0.005V-0.070V in the discharge curve can be read as C1, and the total lithium insertion capacity in the range of 0.005V-2.0V is recorded as C2, and then the lithium insertion capacity proportion of the platform is calculated to be X=44.1%.
[0178] Testing of the compacted density of powder materials :
[0179] Take a certain amount of powder and put it in a special compaction mold, then put the mold on the compaction density instrument, set the pressure to 50000N, and the thickness of the powder under the pressure (thickness after pressure relief) can be read on the equipment. The compaction density can be calculated through ρ=m / v.
[0180] Volume distribution particle size test of materials :
[0181] Dv50 Test:
[0182] The volume distribution particle size Dv50 of the material can be tested by referring to the test method of GB / T 19077-2016 and using the Mastersizer 3000 laser particle size analyzer produced by Malvern Instruments Ltd., UK.
[0183] The secondary batteries prepared in the above examples and comparative examples were tested according to the following method. The results are shown in Table 2.
[0184] Energy density test
[0185] At 25°C, the secondary battery was charged to 3.65V at 1 / 3C constant current, then charged to 0.05C at 3.65V, left to stand for 5 minutes, and then discharged to 2.5V at 1 / 3C constant current, and the battery discharge energy was recorded. The battery discharge energy divided by the battery weight is the battery weight energy density, in Wh / kg. The measurement data is shown in Table 2.
[0186] Table 1
[0187]
[0188] Table 2:
[0189]
[0190] It can be seen from the data in Table 2 that the artificial graphite prepared in Examples 1-6 of the present application has a higher gram capacity and powder compaction density than the artificial graphite prepared in Comparative Examples 1-2, and the secondary batteries of Examples 1-6 have a higher energy density than the secondary batteries of Comparative Examples 1-2. The secondary battery provided by the present application made of artificial graphite with La(110) of 130nm-175nm and Lc(002) of 30nm-42nm has a high energy density.
[0191] Embodiment 7-13
[0192] The preparation methods of Examples 7-13 are similar to those of Example 1, except that the granulating agent used in the preparation steps of artificial graphite and the mass ratio of the shaping material to the granulating agent are adjusted according to the values in Table 3 below.
[0193] The artificial graphite and secondary battery prepared in the above examples were tested according to the following method. The results are shown in Table 3.
[0194] Table 3:
[0195]
[0196] It can be seen from the data in Table 3 that by screening granulating agents with softening points and coking values within a certain range and screening the mass ratio of shaping materials and granulating agents within a certain range, artificial graphite with high gram capacity and high powder compaction density can be further obtained, thereby further improving the energy density of the secondary battery obtained.
[0197] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, wherein the negative electrode film layer comprises a negative electrode active material, characterized in that: The negative electrode active material comprises artificial graphite, wherein La(110) of the artificial graphite is 130nm-175nm, and Lc(002) of the artificial graphite is 30nm-42nm, La(110) represents the crystallite size along the a-axis in the (110) crystal plane of the artificial graphite, and Lc(002) represents the crystallite size along the c-axis in the (002) crystal plane of the artificial graphite.
2. The negative electrode sheet according to claim 1, characterized in that: The La(110) of the artificial graphite is 132nm-172nm, and the Lc(002) is 30nm-36nm.
3. The negative electrode sheet according to claim 1 or 2, characterized in that: La(110) / Lc(002) is 3.5-5.
5.
4. The negative electrode sheet according to claim 3, characterized in that: La(110) / Lc(002) is 4.5-5.
5.
5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The button cell prepared by the artificial graphite was subjected to charge and discharge tests under the conditions of a lithium desorption rate of 0.1C and a lithium insertion rate of 0.05C, respectively, and a charge and discharge curve in the range of 0.005V-2.0V was obtained. In the discharge curve, there was a lithium insertion platform in the voltage range of 0.005V to 0.070V, and the discharge capacity corresponding to the lithium insertion platform accounted for a proportion X of more than 43% of the total discharge capacity of the button cell.
6. The negative electrode sheet according to claim 5, characterized in that: The proportion X of the discharge capacity corresponding to the lithium embedded platform to the total discharge capacity of the button cell is 43%-47%.
7. The negative electrode sheet according to any one of claims 1 to 6, characterized in that: The gram capacity of the artificial graphite is above 359 mAh / g.
8. The negative electrode sheet according to claim 7, characterized in that: The gram capacity of the artificial graphite is 359 mAh / g-366 mAh / g.
9. The negative electrode sheet according to any one of claims 1 to 8, characterized in that: The graphitization degree of the artificial graphite is 94.0%-96.0%.
10. The negative electrode sheet according to claim 9, characterized in that: The graphitization degree of the artificial graphite is 94.2%-95.8%.
11. The negative electrode sheet according to any one of claims 1 to 10, characterized in that: The powder compaction density of the artificial graphite under a pressure of 50000N is 1.95g / cc-2.04g / cc.
12. The negative electrode sheet according to any one of claims 1 to 11, characterized in that: The artificial graphite includes secondary particles.
13. The negative electrode sheet according to any one of claims 1 to 12, characterized in that: The artificial graphite meets one or more of the following conditions: (1) The volume distribution particle size Dv50 of the artificial graphite is 14.5 μm-18.0 μm; (2) The particle size distribution of the artificial graphite (Dv90-Dv10) / Dv50 is 0.9-1.25; (3) The specific surface area of the artificial graphite is 0.8 m 2 / g-2.1m 2 / g.
14. A secondary battery, characterized in that: The invention comprises the negative electrode sheet according to any one of claims 1 to 13.
15. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 14.
16. An artificial graphite, characterized in that: The La(110) of the artificial graphite is 130nm-175nm, and the Lc(002) is 30nm-42nm, La(110) represents the crystallite size along the a-axis in the (110) crystal plane of the artificial graphite, and Lc(002) represents the crystallite size along the c-axis in the (002) crystal plane of the artificial graphite.
17. The artificial graphite according to claim 16, characterized in that The button cell prepared by the artificial graphite was subjected to charge and discharge tests under the conditions of a lithium desorption rate of 0.1C and a lithium insertion rate of 0.05C, respectively, and a charge and discharge curve in the range of 0.005V-2.0V was obtained. In the discharge curve, there was a lithium insertion platform in the voltage range of 0.005V to 0.070V, and the proportion X of the discharge capacity corresponding to the lithium insertion platform to the total discharge capacity of the button cell was more than 43%.
18. The artificial graphite according to claim 16 or 17, characterized in that: The gram capacity of the artificial graphite is above 359 mAh / g.
19. The artificial graphite according to any one of claims 16 to 18, characterized in that: The powder compaction density of the artificial graphite under a pressure of 50000N is 1.95g / cc-2.04g / cc.
20. The artificial graphite according to any one of claims 16 to 19, characterized in that: The artificial graphite includes secondary particles.
21. A method for preparing artificial graphite, wherein: The steps include: Pretreatment step: crushing and shaping the calcined needle coke to obtain a shaped material, wherein the calcined needle coke has a carbon content of more than 97%, a volatile component content of less than 2%, and a sulfur content of less than 0.5%; Granulation step: mixing the shaping material with a granulating agent to obtain a granulated material; Graphitization step: graphitizing the granulated material at 3000°C-3200°C to obtain the artificial graphite with La(110) of 130nm-175nm and Lc(002) of 30nm-42nm, wherein La(110) represents the crystallite size along the a-axis in the (110) crystal plane of the artificial graphite, and Lc(002) represents the crystallite size along the c-axis in the (002) crystal plane of the artificial graphite.
22. The preparation method according to claim 21, characterized in that: The softening point of the granulating agent is 180°C-270°C.
23. The preparation method according to claim 21 or 22, characterized in that: The coking value of the granulating agent is 50%-70%.
24. The preparation method according to any one of claims 21 to 23, characterized in that: The mass ratio of the shaping material to the granulating agent is 100:(6-12).
25. The preparation method according to any one of claims 21 to 24, characterized in that: The preparation method further comprises: Before the graphitization step, the granulated material is subjected to a pre-carbonization treatment to obtain an intermediate.
26. The preparation method according to claim 25, characterized in that: The temperature of the pre-carbonization treatment is 1000-1500°C and the time is 1-4 hours.
27. The preparation method according to any one of claims 21 to 26, characterized in that: The preparation method further comprises: after the graphitization step, subjecting the artificial graphite to surface micro-oxidation treatment.
Citation Information
Patent Citations
Modified graphite, preparation method, and secondary battery and electric device containing modified graphite
CN115838170A
Negative electrode material, secondary battery, and electronic device
CN117882216A
Method for testing gram volume of graphite
CN117890802A
Carbon material and preparation method therefor, and secondary battery and electric device comprising same
WO2024108574A1